The characteristics, changes and effects of building elements in the two-storey public low cost housing on the Malay culture core - Abdul Rahim, Zaiton (2000)
The culture core of the inhabitants has been found to influence the building elements in house design, especially in creating a supportive living environment for the inhabitant's lifestyle. The changes in the culture core of the inhabitants have also been found to influence the changes in the building elements. However, this is not the case in low cost housing because generally the inhabitants have no control over the design. Studies have shown that the low cost housing designs lack the cultural aspects of the inhabitants. The result is that the inhabitants have to adapt their culture core with the physical shell of the houses until modifications are done on the houses. In this process, some of the important aspects of the culture core were either compromised or lost. Using analytical review, content analysis and case study, this study analyses the characteristics, changes and the effects of the building elements on the Malay culture core in the two storey public low cost housing. Analytical review involves a detail analysis of the characteristics of the building elements in the traditional Malay house as the baseline. Content analysis analyses the characteristics and changes in the building elements of the public low cost housing designs and finally six case studies were employed to evaluate the effects of the building elements on the Malay inhabitants' culture core. The results indicated that the characteristics and the changes in the building elements were not congruence with the changes in the culture core of the Malay inhabitants. The results also showed that the inhabitants were unable to practice their lifestyle according to the culture core. As such, the study suggested that the design of the low cost housings be improved by including the important aspects of the inhabitants' culture core.